Estimating Trade Facilitation in a Regional Integration Initiative: Leveraging the Logistics Performance Index - Kikerkova, Irena; Trpeski, Predrag; Kocev, Ljuben; Tonovska, Jasna (My University, 2024)
This study examines trade determinants, with a particular focus on logistics within the context of a regional integration initiative. A gap in the literature concerning the application of gravity models to the TRACECA initiative is identified through the literature review. Subsequently, an analysis of the legal framework underpinning TRACECA is undertaken. Utilizing the World Bank’s Logistic Performance Index (LPI) within a gravity model framework, the study evaluates the impact of trade facilitation within the TRACECA region. Findings indicate positive associations between trade and GDP, common language, and shared borders, while distance exerts a negative influence. The research underscores the role of the LPI in facilitating trade within TRACECA, advocating for collaborative endeavors to enhance logistics, remove latent barriers, and streamline customs procedures. Furthermore, the study advocates for increased investment to strengthen TRACECA’s trade facilitation initiatives, emphasizing the necessity of mutual political commitment to advance regional trade.
Keywords: Trade Facilitation; Trade Logistics; Gravity model; Logistic Performance Index (LPI); TRACECA